Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 781 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Chiroxiphia lanceolata (Wagler, 1830)", { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Material sample" ] } ] } The dataset includes 781 records from 40 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006855-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences